ANALISIS SISTEM INFORMASI KEBERHASILAN WEBSITE SIAP PPDB ONLINE DINAS PENDIDIKAN PROVINSI JAMBI DENGAN METODE DELONE AND MCLEAN - Santoso, Heri; Akbar, Zulfikri; Helmina, Helmina (LPPM Universitas Muhammadiyah Jambi, 2022)
The PPDB ONLINE website is one of the applications of information technology that is used to make it easier for users to obtain information related to New Student Admission (PPDB), with services provided by the Jambi Provincial Education Office. The researcher analyzes the success rate of the PPDB ONLINE website in Jambi Provincial Education Office using the Delone and Mclean methods and finds out the effect of the independent variables (quality of the system, quality of information, quality of services provided) on the dependent variable (usage, user satisfaction, net benefits) using the SEM method. and SmartPLS software. This study resulted in 6 accepted hypotheses from 9 proposed.